Insights on the association between somatic aneuploidy and ostreid herpesvirus 1 detection in the oysters Crassostrea gigas, C. angulata and their F1 hybrids. (11th October 2014) - Batista, Frederico M; López‐Sanmartín, Monserrat; Boudry, Pierre; Navas, José I; Ruano, Francisco; Renault, Tristan; Fonseca, Vera G; Leitão, Alexandra
Abstract: Cytogenetic abnormalities associated with viral infections, including from viruses of the Herpesvirales order, have been reported in vertebrate species. Ostreid herpesvirus 1 (OsHV‐1) has been detected worldwide during mortality outbreaks of the Pacific oyster Crassostrea gigas . On the other hand, a high proportion of aneuploid cells in somatic tissues have been observed in C. gigas . In this study, we analysed the putative association between aneuploidy levels and the detection of OsHV‐1 in gills of C. gigas, the Portuguese oyster C. angulata and their F1 hybrids cultured in Ria Formosa (Portugal). OsHV‐1 was detected by PCR in 5.4% of the total of oysters analysed ( n = 111) namely in 11.1%, 8.0% and 1.7% of C. gigas, C. angulata and F1 hybrid respectively. Sequencing analysis of a viral fragment amplified with the C2/C6 primer pair revealed a high similarity with the OsHV‐1 reference type. Moreover, in situ hybridization confirmed the presence of OsHV‐1 in gill tissue. Oysters where OsHV‐1 was detected had a significantly higher mean percentage of aneuploid cells (25%) than the ones where the virus was not detected (18%). However, the overall low percentage of positive samples contrasted with the high mean percentage of aneuploidy observed, with 50% of the oysters analysed showing a percentage of aneuploid cells between 20% and 30%. We hypothesize that somatic aneuploidy may adversely affect oysters making them more prone to OsHV‐1 infection, but the virus is unlikely to be the cause of somatic aneuploidy.